Public housing as urban heritage: experience and research approach in Spain - Cervero Sánchez, Noelia (2022)
International conservation policies have incorporated the urban dimension of heritage, which considers the city as a historical continuum connected with the territory. However, the social housing complexes built in Europe throughout the second half of the 20th century lack legal entities and tools for their protection. Urban rehabilitation policies have substituted the initial demolition-replacement processes, by way of combining and coordinating protective measures. The rehabilitation of the Caño Roto Housing Estate (Madrid 1994-2004), as a precursor of a type of intervention widespread in Spain, is analysed with the aim of finding the actors, tools and decisions, so that the model can be optimised in future operations. The heritage dimension involves the development of the necessary means to make possible the conservation and functional updating of the buildings, as well as the development of new cultural, socioeconomic and environmental values, in order to add sustainability to the urban environment.